‘Halo Dek’: Analisis Wacana Kritis atas Praktik Komunikasi Oknum Aparat dalam Upaya Berkenalan dengan Wanita di Media Sosial - Rebecca, Renny (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2026)
This research analyzes the "Halo Dek" phenomenon on TikTok as a digital communication practice that reflects power relations, gender ideology, and the dynamics of popular culture in Indonesia. This simple greeting, when used by TNI and Polri officers to get acquainted with women, experienced a shift in meaning to become a symbol of flirtatious behavior and a representation of excessive masculinity. Using a qualitative approach using Norman Fairclough's Critical Discourse Analysis method, this research examines three dimensions of analysis: text, discourse practice, and social practice. Data was obtained from videos, screenshots of conversations, and public comments on the theme "Halo Dek" which were selected through purposive sampling. The research results show that the phrase "Halo Dek" functions as an arena for a battle of meaning between the language of domination and resistance, where the public—especially women—uses humor, irony, and virality as a strategy to criticize patriarchal communicative behavior. In conclusion, this phenomenon reflects a shift in symbolic relations between the state and citizens, as well as the emergence of a form of linguistic emancipation that shows women's ability to seize control of the narrative and redefine communication ethics in the digital space.